Peranan Teknologi Dalam Pertumbuhan Sektor Transportasi Dan Komunikasi Di Indonesia : 1977-2007 - Alkadri, Alkadri (Warta Penelitian Perhubungan, 2010)
Application of technologtj in economic development of a nation spread across various eronomic sectors,including transportation and communication sector. In Indonesia, the progress achieved bytransportation and communication sector-especially in terms of value added grawth- over the lastthree decades can not be separated from the role of technological progress in this sector. By using t.otalfactor productivihj (TFP) approach as a indicator for the role of technological progress, this papertries to calculate and analyze how much the role of technological progress in the grawth of transportationand communication sector. Calculation method used is growth accounting method whichapplied to the Cobb-Douglas production function. The calculations shaw that during the period1977-2007 transportation and communication sector achieved grawth rate m;erage 7.77% per year,where 2.29% of which came from the contribution of technological progress (TFPG). The role of thistechnology is greater than the role of labor grawth (1.85%), but slightly belaw the role of capitalgrowth (3.63%). These results imply that the development of technology in transportation andcommunication sector must be increased again in the coming years in order t.o encourage the growthof transportation and communication sect.or higher.Keywords : Tecknologi, Transportataion and Komunication, Total Factor ProductivihJ